If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 12 = x + -4 Reorder the terms: 12 + 9x = x + -4 Reorder the terms: 12 + 9x = -4 + x Solving 12 + 9x = -4 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 12 + 9x + -1x = -4 + x + -1x Combine like terms: 9x + -1x = 8x 12 + 8x = -4 + x + -1x Combine like terms: x + -1x = 0 12 + 8x = -4 + 0 12 + 8x = -4 Add '-12' to each side of the equation. 12 + -12 + 8x = -4 + -12 Combine like terms: 12 + -12 = 0 0 + 8x = -4 + -12 8x = -4 + -12 Combine like terms: -4 + -12 = -16 8x = -16 Divide each side by '8'. x = -2 Simplifying x = -2
| 8-2(-5+4)=10 | | y-2=-.25(x-4) | | -12+k=28 | | 5x+3=12x+15 | | 7-2x+6=4x-5 | | (4x-2)*(x+2)*0.5= | | 2n-3=5n+12 | | 25+1x=4+8x | | H(0)=x^2-6x+5 | | 5[x-2]=30 | | (4x-2)*(x+2)= | | s+2[s+3]+[4s-5]=148 | | 5x-22=77 | | 2y+2x^2=8x-8 | | y-0=.5(x-0) | | ax+5bx=7a-c+2ax | | 8x-10=85 | | -3=7-y | | 666666666666666666666666666666666666666666666666666666666666666666666666666666666666666666666666666666+9d=2.88 | | -2(5y-10)-y=-4(y-3) | | 14-2(x+8)=5x-(3-34) | | 3(x-5x)=60 | | 5a+6-3a=7a-4 | | x-13+83=180 | | (10-2)-2(1+3)=y | | 6(2x-5)-6=12x-36 | | -5m^3(7n^4-2mn^3+6)= | | z(-5-5*-5)=60 | | 5t=24.5 | | y-0=-4(x+5) | | 17x+3=4(4x+5) | | z(-5-5*-5)=45 |